Clifford the big red dog : the show-and-tell surprise - Margulies, Teddy Slater; Haefele, Steve (New York : Scholastic, 2001)
Emily Elizabeth can't find anything special enough for show-and-tell, until Clifford gives her an idea.
H
"From the television script 'Best friends' by Lois Becker and Mark Stratton; based upon the storybook character by Norman Bridwell."
b
b
Keywords: Dogs -- Fiction; Show-and-tell presentations -- Fiction; Schools -- Fiction